Responses to drought stress modulate the susceptibility to plasmopara viticola in vitis vinifera self-rooted cuttings - Heyman, Lisa; Chrysargyris, Antonios; Demeestere, Kristof; Tzortzakis, Nikos G.; Höfte, Monica (My University, 2021)
Climate change will increase the occurrence of plants being simultaneously subjected to drought and pathogen stress. Drought can alter the way in which plants respond to pathogens. This research addresses how grapevine responds to the concurrent challenge of drought stress and Plasmopara viticola, the causal agent of downy mildew, and how one stress affects the other. Self-rooted cuttings of the drought-tolerant grapevine cultivar Xynisteri and the drought-sensitive cultivar Chardonnay were exposed to full or deficit irrigation (40% of full irrigation) and artificially inoculated with P. viticola in vitro or in planta. Leaves were sampled at an early infection stage to determine the influence of the single and combined stresses on oxidative parameters, chlorophyll, and phytohormones. Under full irrigation, Xynisteri was more susceptible to P. viticola than the drought-sensitive cultivar Chardonnay. Drought stress increased the susceptibility of grapevine leaves inoculated in vitro, but both cultivars showed resistance against P. viticola when inoculated in planta. Abscisic acid, rather than jasmonic acid and salicylic acid, seemed to play a prominent role in this resistance. The irrigation-dependent susceptibility observed in this study indicates that the practices used to mitigate the effects of climate change may have a profound impact on plant pathogens.
Keywords: Climate change; Irrigation; Abiotic stress; Biotic stress; Grapevine; Downy mildew; Phytohormones; Oxidative stress; Abscisic acid